Adoption and risk management of bimodal IT outsourcing service: review and directions for future research. (17th October 2019) - Mao, Hongyi; Gong, Yeming; Liu, Shan; Zhang, Yajun; Li, Kunyu
The rapid pace of technological change in the internet age has fundamentally transformed information technology (IT) outsourcing. Thus, organisations should be able to re-imagine their IT outsourcing strategies to meet the needs of increasingly turbulent business environments. Bimodal IT requires the shaping of IT services to be either agile oriented or efficient oriented, thereby bringing new demands to an organisations' adoption strategies. On the basis of the review of traditional IT outsourcing service research, this paper presents the traditional and nonlinear modes of IT outsourcing service, discusses risk-based IT outsourcing service adoption strategy, relationship and contract management strategies from the static and dynamic perspectives and provides several directions for future research.